Juridical Review of Pretrial Proceedings Against the Determination of a Suspect in the Crime of Maltreatment - Ritian Handayani; Yasmirah Mandasari Saragih (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2025)
Examination of a criminal case in a judicial process essentially aims to find the material truth, namely the complete truth of a criminal case by applying the provisions of criminal procedural law honestly and in a timely manner with the aim of finding out who the perpetrator is who can be charged with committing something. violation of law. Making a post mortem et repertum gives the full duty to the doctor as an implementer in the field to assist the prosecutor in determining the direction of the charges that will be brought against the defendant, as well as assisting the judge in finding the material truth in deciding the criminal case. This research includes normative legal research, so the legal materials used are primary, secondary and tertiary legal materials. The technique for collecting legal materials that will be used as a source in this research is library research, namely collecting legal materials by reading statutory regulations, official documents, journals, articles from the internet, and other literature that is closely related to The issues discussed are based on secondary legal materials. The presence of the Pretrial Institution provides a warning that law enforcers must be careful in carrying out their legal actions and every legal action must be based on applicable legal provisions, meaning that they must be able to exercise restraint and distance themselves from arbitrary actions. Thus, it is clear that organizing pretrial proceedings is not an easy task considering that the activities of one law enforcement agency to assess and test the work patterns of other law enforcement agencies is definitely work that must be carried out carefully and mastering all law enforcement mechanisms. The judiciary in Indonesia, one of whose tasks is to examine laws against the constitution, is what we often call judicial review. This judicial review is carried out to protect the rights of citizens who feel disadvantaged by the enactment of a law. In this case, what concerns the author is the judicial review of article 77 of the Criminal Procedure Code, which in this article is felt to be detrimental to someone who is designated as a suspect by investigators, because the article does not regulate the determination of suspects as pre-trial objects.